Asia in Europe, Europe in Asia - Rutten, Mario; Ravi, Srilata; Goh, Beng-Lan (Book collections on Project MUSE., 2004)
The book presents a unique combination of the study of contemporary and historical practices between Asia and Europe and brings forth some of the latest thinking on the subject. Recent debates have centered primarily on contemporary aspects of the Europe-Asia partnership in terms of international relations and economic linkages. The present volume complements this political and economic interest in Europe-Asia relationship by focusing on the academic, social and cultural connections between the two regions. The contributions in this volume have a contemporary focus but contextualize the themes within a historical perspective. They deal with academic discourses on the region, on modernity and entrepreneurship; they discuss the long-term exchange of knowledge in specific scientific fields; and they focus on the cultural interconnections in the area of film, literature and migration. The originality of this book lies in its interdisciplinary approach to the question of Asia-Europe and in its emphasis on the multifaceted complexity of the relationship between these two regions. It brings together the diversity of local histories, ideas, and agencies in both Europe and Asia into a universal project of knowledge formation in order to reveal their contribution to the making of the world we are in. Contributors: Syed Farid Alatas, Gregory Clancey, John Kleinen, Van Nguyen-Marshall, Henk Schulte Nordholt, Paravin J. Patel, Maurizio Peleggi, Satish Saberwal, Vineeta Sinha.